Cognitive and emotional benefits of individual reminiscence therapy in elderly stroke survivors: study protocol for a randomized controlled study - Shan Wang; Miaomiao Hu; Yehua Xue; Yeping Chen; Kunpeng Li; Lu Dong; Libing Liang; Jieting Jiang; Xuemin Li; Caiqin Wu (BMC Psychology)
Abstract Background Post-stroke cognitive impairment (PSCI) and depression affect over 60% of elderly stroke survivors, severely impairing functional recovery and quality of life. Despite the efficacy of non-pharmacological interventions, evidence on individualized approaches for elderly stroke patients remains limited. This study aims to evaluate the clinical impact of individual reminiscence therapy (RT) on cognitive function, depressive symptoms, and quality of life in elderly stroke survivors. Methods A single-blinded, parallel, randomized controlled trial will be conducted with 80 elderly stroke patients recruited from two hospitals in Shanghai. Participants will be randomly assigned to an intervention group receiving eight weeks of individual RT (30–45 min weekly) or a control group receiving standard care with a 1:1 ratio. Cognitive function, including Mini-Mental State Examination (MMSE), Boston Naming Test (BNT), Trail Making Test-A (TMT-A), depressive symptoms assessed by the Patient Health Questionnaire-9 (PHQ-9), and quality of life assessed by the Stroke-Specific Quality of Life Scale (Ss-QoL) will be assessed by blinded evaluators at baseline (T0), post-intervention (8 weeks, T1), and 4-week follow-up (12 weeks, T2). The intervention features a tailored RT protocol allowing patients to select topics (e.g., childhood memories, work life) to enhance engagement. Blinded evaluators will ensure measurement objectivity, and intention-to-treat analysis addressed attrition. Discussion This study aims to provide a fresh perspective on the effectiveness of individual RT in enhancing cognitive function, reducing depressive symptoms, and improving the quality of life, among stroke patients. The use of a tailored individual RT program based on an in-depth literature review and conceptual analysis, along with a multidimensional assessment system, differentiates this study from previous ones. Trial registration This protocol was registered at the Chinese Clinical Trials.gov (Identifier: ChiCTR2500095471) on January 8, 2025.